Outbreaks of Foodborne Illness Associated with Melons - Michelle D. Danyluk; Rachel McEgan; Ashley N. Turner; Keith R. Schneider (EDIS, 2014)
Despite the manner in which they are prepared, melons are commonly consumed raw without a processing step which would eliminate pathogenic bacteria. For those concerned about the safety of melons, including cantaloupe, honeydew, and watermelon, this 6-page fact sheet lists outbreaks associated with melons in the United States, Canada, and Europe, along with information about the location, pathogen, and incidence of illness. Written by Michelle D. Danyluk, Rachel McEgan, Ashley N. Turner, and Keith R. Schneider, and published by the UF Department of Food Science and Human Nutrition, November 2014. (UF/IFAS Photo by Thomas Wright)